2017
DOI: 10.3390/en10121993
|View full text |Cite
|
Sign up to set email alerts
|

Sludge Acts as a Catalyst for Coal during the Co-Combustion Process Investigated by Thermogravimetric Analysis

Abstract: Sewage sludge in China has the characteristics of low organic content and low heating value compared with other developed countries. Self-sustaining combustion of Chinese sludge cannot be achieved when the moisture content is high. Co-combusting a small amount of sludge in the existing coal-fired boilers is a usual sludge disposal method in China. Thermogravimetric (TG) and differential scanning calorimetry (DSC) analysis of a bituminous coal, three different sewage sludges, and their blends have been carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The TG curves of CG and PVC can be roughly divided into three stages under an air or nitrogen atmosphere. The results of the three stages of weightlessness mass of CG are consistent with those from the aforementioned studies [47,15]; therefore, only the experimental results of PVC combustion and pyrolysis are analyzed.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The TG curves of CG and PVC can be roughly divided into three stages under an air or nitrogen atmosphere. The results of the three stages of weightlessness mass of CG are consistent with those from the aforementioned studies [47,15]; therefore, only the experimental results of PVC combustion and pyrolysis are analyzed.…”
Section: Resultssupporting
confidence: 77%
“…Owing to its ignition difficulty, unstable combustion, and low calorific value [3], researchers worldwide have investigated the combustion and co-combustion characteristics of CG. Recently, the co-combustion characteristics of CG was discussed in terms of the various properties of coal rather than non-coal substances [47]. Several scholars have conducted research on the co-combustion characteristics of CG with coal gas [8–12]; their results showed that the mixing ratio is the most important parameter to consider when optimizing the efficiency of co-combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these reactions can involve interactions with heavy metals, as most of the organic volatiles were decomposed during the main oxidation process. Overall, oxidation is the longest stage with more than 60% of weight loss between 200 and 600 • C. Figure 3A further showed a relatively small weight loss at temperatures higher than 800 • C. According to Chen et al [48], this last stage corresponds to the burnout stage. Magdziarz and Wilk [49] suggested that the burnout happens due to the small part of the carbon left in the sample [49].…”
Section: Thermogravimetric Analysis Of the Ss And The Blends With Coalmentioning
confidence: 74%
“…Magdziarz and Wilk [49] suggested that the burnout happens due to the small part of the carbon left in the sample [49]. However, Chen et al [48] argued that the burnout stage corresponds to the decomposition of the remaining CaO, as reported to be 18.9 wt%, within the sludge as has been proposed by Folgueras et al [30]. Regression was performed for the data presented in Figure 3 and is available in the Supplementary Material (Figure S1, Equations (S1)-(S4)).…”
Section: Thermogravimetric Analysis Of the Ss And The Blends With Coalmentioning
confidence: 99%
“…The research of mathematical models should be further development. Thermal behavior of fuel has been widely studied by thermogravimetric analysis (TGA), which is an extensive and effective research method for studying thermal behavior [8][9][10][11][12]. Thermal characteristics of ignition temperature, burnout temperature, maximum combustion rate, and combustion kinetic parameters can be acquired to quantitatively analyze the thermal process of fuel [13][14][15].…”
Section: Introductionmentioning
confidence: 99%